Remittances, Gender, and Global Care Chains: The Case of the Latin American Population in the Basque Autonomous Community - Barba del Horno, Mikel; Garcia-Azpuru, Amaia; Arcos-Alonso, Asier (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2024)
This article examines the determinants of remittances sent by the Latin American population residing in the Basque Autonomous Community (CAE), with a particular focus on gender differences. Utilizing data from the Survey of Foreign Immigrant Population, logistic regression and linear regression procedures were employed to assess the factors influencing remittance sending and the amount of remittances sent. The findings reveal that while the explanatory factors for remittances among men align with the literature on remittance determinants, women’s remittance behavior is better understood through a critical framework such as the Global Care Chains theory.